A proposed approach for preventing Cross-Site Scripting - Taha, Twana Assad; Karabatak, Murat (Ieee, 2018)
In this paper, the great threat Cross-Site Scripting (XSS) is introduced that faced with the web pages. Because of the impacts of such web threats during design and developing web pages, web developers must be aware and have adequate knowledge about varies type of web attacks and how to prevent or mitigate them. Web developers should have knowledge about how attackers attack websites and exploit weak points on websites during filling forms, registering and opening suspicious links or attachments in emails. The important of this subject is to provide great details and information about identifying impacting and protecting from these types of web threats. It aims to provide both web developers and users with enough knowledge while developing and using websites to prevent from such attacks and reduce them impacting and protecting from these types of web threats. It aims to provide both web developers and users with enough knowledge while developing and using websites to prevent from such attacks and reduce them. In this paper use PHP's functions to evaluate the efficiency of web pages for implementing it and to prevent XSS attack.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: component: Web application Security; Injection threats; input validation